THE IMPLEMENTATION OF MULTIPLE INTELLIGENCE CONCEPT BASED ON ISLAMIC WORLDVIEW AT SMP AL-WASHLIYAH 8 MEDAN - Arifin, Hairul; Husaini, Adian; Mujahidin, E (Tawazun: Jurnal Pendidikan Islam, 2018)
The education process is an effort to develop and actualize learners according to their talents and interest. Learning system representative, the input, process, and output-based fulfillment and development potential of each element contained in a human being. Multiple Intelligences explained 9 kinds of human intelligence include intelligence languages, musical, logical-mathematical, visual-spatial, body kinesthetic, intrapersonal, Interpersonal, naturalist and existence. This study applied a qualitative, method. SMP al-Washliyah 8 Medan is the only school built at the University of al-Washliyah that applies the concept of Multiple Intelligences. Application of Multiple Intelligences in SMP al-Washliyah 8 globally covers three important stages, namely input, process and output. Design Concept of Multiple Intelligences in SMP al-Washliyah 8 Medan is the improvement quality input and output. The school change the moral quality of the academic and students. The study of theory used learning process improvement. The formula is the teaching style of the teacher should be the same as the student's learning style, the teacher should know how the student's learning style by making the results of MIR (Multiple Intelligences Research) as a guide for teaching. Keywords : Multiple Intelligence, Islamic Worldview.